Borrowing As A Tool To Fill The Ideological Thoughts: The Role Of Code-Mixing In An American Brat By Bapsi Sidhwa And The Escape By Qaisra Shiraz - Mirza Noman Shamas (University of Chitral Journal of Linguistics and Literature, 2019)
This research article highlights the temperament, inference, scope, and motives ofcode mixing in Pakistani English works. One novel from Pakistani English novelsnamely, An American Brat by Bapsi Sidhwa and one short story namely, TheEscape by Qaisra Shehraz are being selected as an illustration of this reading. Inthis novel and short story the writers have already dealt with the characteristics ofpost colonialism. English language and literature pierced into the privilegedcivilizations of the sub-continent, after the end of British Imperialism. Pakistaniwriters in English are the best interpreter of the post-colonial communal language.In this study, I have hit upon code mixing in English works written by Pakistaniauthors to a bigger echelon. These works are paragons of arts and theunbelievable mixture of rhetorical and fictitious study. In these works the writershave not abased the confined diversities. They have tinted the value of PakistaniEnglish in order to achieve the chatty desires of native people. These borrowingsfrom the native languages are used to fill the lexical fissures of ideologicalthoughts. The reason of these borrowings is not to represent the English assubstandard assortment. Through the utilization of native words we conclude thatthe significance of native languages has been tinted to question mark the dialectas well. The words of daily use also have an area of research for English peoplewithout having any substitute in English. That’s why in English literatureinnovative practices and ideas of code-mixing have been employed.